Analysis of Salt Forms used in Siddha Medicine - Rakulini, S.; Sounthararajan, K. (University of Colombo, 2024)
Introduction Salt, a crucial element in human life, is derived from the earth, seawater, or plants. It has antiperiodic, emetic, laxative, stomachic, and vermifuge properties. Diet regulation (Pathiyam) is crucial in Siddha Medicine, and includes two types: Itchapathiyam and Kadumpathiyam. Kadumpathiyam applies to medicines containing mercury. Objectives This study aimed to scientifically assess the various salt forms used in siddha medicine, including salt, fried salt, salt fried with Clerodendrum inerme, and Azima tetracantha. Methods Four samples were analyzed. There are salt (S1), fried salt (S2), salt fried with leaves of Clerodendrum inerme (S3), and Azima tetracantha (S4). Physicochemical assessment, scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and high-performance thin-layer chromatography (HPTLC) were performed on all four samples. Results These results indicate that all four samples exhibited similar properties. The samples were dissolved in water. FTIR spectroscopy is a valuable tool for determining the structural features of compounds and their bonding environments. In S1, a broad absorption peak was assigned to the O-H stretching vibration, indicating the alcohol characteristics. In S2, an aromatic NH2 vibration frequency was observed, indicating primary amine characteristics. In S3, a broad absorption peak was observed for the alcohol characteristics, whereas in S4, a broad absorption peak was observed for the O-H stretching vibrations. The HPTLC fingerprinting analysis of S3 and S4 revealed six and eight prominent peaks, respectively, indicating the presence of versatile phytocomponents. Conclusion The combination of spectroscopic and chromatographic techniques facilitated a comprehensive understanding of the chemical composition of the samples. Further analyses can offer valuable insights into the specific pharmacological actions of these compounds.
Keywords: Salt; Pathiyam; Diet; Clerodendrum inerme; Azima tetracantha; Siddha medicine